The Ability of Conservation Agriculture to Conserve Soil Organic Carbon and the Subsequent Impact on Soil Physical, Chemical, and Biological Properties and Yield - Page, Kathryn Louise; Dang, Yash P.; Dalal, Ram C. (Frontiers in Sustainable Food Systems, 2020)
Increases in human populations and the emerging challenges of climate change mean that the world's agricultural systems will need to produce more food in an environment that is increasingly variable and where the quality of our natural resource base is declining. One central measure of an agricultural system's capacity to do this is its ability to preserve soil organic carbon (SOC), due to the pivotal role that this plays in maintaining soil physical, chemical, and biological properties and ultimately yield. This narrative review examines the literature published worldwide over the last 30 years to assess the impact of one widely applied agricultural management system, conservation agriculture (CA), on its ability to maintain SOC and the subsequent impacts on soil physical, chemical and biological properties, and yield. While the effects of CA on SOC worldwide are variable, with both increases and decreases observed, in regions where soil and climatic conditions are favorable for biomass production and where the system does not negatively impact yield, then CA can lead to higher amounts of SOC relative to conventionally managed systems, particularly in the surface of the soil profile. Where greater SOC occurs, these are also often accompanied by improvements in soil structure, water infiltration and soil water storage, plant nutrient availability, microbial biomass and diversity, and yield. However, where CA is used in certain environments (e.g., cold, wet environments with poorly drained soils) or where the CA system has not been well-adapted to local conditions, taking into account the specific agronomic, social, and environmental challenges present, then it may not be a successful system of management. Farmers require access to a range of tools and resources to allow them to identify if the principles of CA are likely to lead be appropriate for their situation and well-designed, locally adapted systems to successfully overcome the agronomic, social and economic challenges that can be associated with its use.